2012
DOI: 10.1167/iovs.12-9919
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Myopic Maculopathy in Elderly Chinese: The Shihpai Eye Study

Abstract: The prevalence of high myopia and myopic maculopathy in this elderly Chinese population group was high. Of the major risk factors examined, high systolic blood pressure may be associated with myopic maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
86
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 33 publications
18
86
1
Order By: Relevance
“…These findings should correspond to the findings of previous studies that have reported partial loss of the choriocapillaris, occasional sporadic large choroidal vessels remaining in diffuse atrophy and complete loss of the choriocapillaris that leads to the absence of the outer retina and RPE in patchy atrophy 1 2…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings should correspond to the findings of previous studies that have reported partial loss of the choriocapillaris, occasional sporadic large choroidal vessels remaining in diffuse atrophy and complete loss of the choriocapillaris that leads to the absence of the outer retina and RPE in patchy atrophy 1 2…”
Section: Discussionsupporting
confidence: 89%
“…Myopic maculopathy, one of the most severe complications of highly myopic eyes, induces severe visual impairment 1 2. Curtin and Karlin first defined myopic maculopathy that included chorioretinal atrophy, a central pigment spot, lacquer cracks, posterior staphyloma and optic disc changes 3.…”
Section: Introductionmentioning
confidence: 99%
“…High myopia is usually defined as those eyes with a refractive error of ≥−6.0 diopter, however myopic retinochoroidal atrophies do not occur in all eyes with these higher refractive errors. Similarly, myopic retinochoroidal atrophy often occurs in myopic eyes with longer axial lengths but not in all of these eyes [5]. A tessellated fundus is a common characteristic of myopic eyes, and has been found to be an important clinical marker for the development of retinochoroidal changes [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, myopic retinopathy was defi ned as the presence of lacquer cracks, focal area of deep choroidal atrophy and macular choroidal neovascularization, or geographic atrophy in the presence of high myopia. Signs of myopic retinopathy were present in 32 (72.7 %) of the 44 high myopic adults, representing a prevalence of 3.0 % [ 55 ]. These studies cannot be directly compared primarily because the defi nitions of myopic retinopathy are different and there are variations in the characteristics of study participants (e.g., the age and proportion of either gender) and differences in the methodology or study design (e.g., the defi nition of myopic retinopathy) including sampling strategies and response rates.…”
Section: Prevalence Of Myopic Retinopathymentioning
confidence: 99%